A jojoba (Simmondsia chinensis) seed cake extracts express hepatoprotective activity against paracetamol-induced toxicity in rats - Firas Feki (17545638) (2022)
This study aimed to investigate the hepatoprotective activity of jojoba seed cake extracts against an acute paracetamol (PC) intoxication. Two aqueous extracts from jojoba (Simmondsia chinensis) seed cake, a simmondsin-rich extract (WE), and a simmondsin-hydrolyzed extract (NE) using Viscozyme L enzyme have been prepared and characterized. After enzyme treatment, simmondsin content decreased from 33.0 % to 3.0 % and glucose content increased from 16.2 % to 27.3 % reflecting simmondsin hydrolysis. Both extracts were administered to different rat groups via gavage (0.6 g/kg b.w.) before PC treatment (2 g/kg b.w.) three times a week for 3 weeks. The PC intoxication altered the serum biomarkers, the oxidative status, and the Tumor necrosis factor alpha (TNF-α), Bax and Bcl-2 protein expressions of tested animals. In addition, the histological analysis of liver tissues proved significant injury and hepatocellular necrosis. WE and NE extract showed a relatively high in vitro radical scavenging (ORAC) and averting activities (HORAC) with a polyphenol content of 3.6 % and 2.9 %, respectively. Both extracts showed a powerful in vivo hepatoprotective activity against PC-induced toxicity by improving the hepatocellular antioxidant status and blocking proteins expression (TNF-α, Bax and Bcl-2), involved in inflammation and liver damage. However, the enzymatic treatment improved the hepatoprotective activity of NE despite its lower simmondsin content and lower in vitro antioxidant capacity. This enhancement could be linked to the synergetic effect between the antioxidant components and the new hydrolytic products as glucose, uronic acids, arabinose and simmondsin-aglycons. These results suggest that jojoba waste could be potentially valorized in developing hepatoprotective drugs. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2022.113371